Grundsätze über die Anlagen neuer Sternwarten - Mit Beziehung auf die Sternwarte der Universität Göttingen. Von Georg Heinrich Borheck - Beuermann, Klaus (Universitätsverlag Göttingen, 2005)
The Göttingen Observatory, workplace of the famous scholar Carl Friedrich Gauss, is an important architectural monument. In 2005, it has been reconstructed jointly by the Georg-August-University and the Academy of Sciences in Göttingen. Since then it serves as a representative building for the University and is the seat of the Academy. With the use of the historic rooms for exhibitions this imposing building is open to the public for the first time. 200 years ago the observatory represented the recent scientific findings of its time and moved the University of Göttingen into the leading group of the foremost research institutions in Europe at this time. Also due to its architecture it has been a big leap for Georg Heinrich Borheck, architecture of the University of Göttingen. The war of the Napoleonic era disrupted the attempt of Borheck to publish his description of the construction of the Göttingen observatory in 1805. But his writing is still relevant today and will be finally published with this band for the first time accessible to a wide public. It shows the principles on which public buildings were designed then, explains the importance of the construction in art- and science-historical perspectives and informs on the plans for the restoration of the observatory in a separate article and in the preface by the President of the Georg-August University Prof. Dr. Dr. hc Kurt von Figura.